Evaluation of organoleptic indicators of fried mushrooms depending on the duration of temperature influence - Rudakova, A. A. (ТДАТУ, 2020)
The aim of the work was to determine the optimal time of heat treatment during the preparation of the dish "mushrooms fried with soy sauce and sour cream" for three types of mushrooms: lung oyster Pleurotus pulmonarius (Fr.) Quél. and new for the Ukrainian market - golden oyster mushroom (Pleurotus citrinopileatus Singer) and beech mushroom (Hypsizygus tessellatus (Bull.) Singer,), known as "buna shimeji".
Keywords: mushroom raw materials are processing; species of mushroom; the optimal time of heat treatment